Pengaruh Fraud Diamond Terhadap Fraudulent Financial Statement - Moch Hilmi Silham; Pupung Purnamasari; Nopi Hernawati (Bandung Conference Series: Accountancy, 2023)
Abstract. With the increasingly complete implementation of components in financial reporting in Indonesia, there are still significant opportunities for management and other stakeholders to be involved in fraudulent activities in financial reporting. Therefore, this study aims to investigate the traces of fraud diamonds for the detection of fraud in financial reporting in industrial banking companies listed on the Indonesia Stock Exchange between 2018 and 2021. This research uses panel data regression methodology, using data consisting of a total of 120 samples. This study examines various variables, including the pressure variable put forward by the financial objectives proxy, as well as the rationalization variable put forward by the TATA proxy, which have a positive effect on the possibility of fraudulent financial reporting. However, the opportunity variable represented by the DBOUT proxy and the capability variable represented by the DCHANGE proxy are not proven to have an effect on the possibility of fraudulent financial reports. Abstrak. Dengan semakin lengkapnya penerapan komponen dalam laporan keuangan di Indonesia, masih terdapat peluang yang signifikan bagi manajemen dan pemangku kepentingan lainnya untuk terlibat dalam aktivitas kecurangan dalam pelaporan keuangan. Pengujian ini dilakukan untuk mengetahui seberapa besar dampak fraud diamonds terhadap pendeteksian kecurangan pada pelaporan keuangan terhadap perusahaan industri perbankan yang ada diBursa Efek Indonesia ditahun 2018 sampai 2021. Penelitian ini menggunakan metode regresi data panel, menggunakan data yang terdiri dari total sebanyak 120 sampel. Penelitian ini mengkaji berbagai variabel, antara lain variabel tekanan yang diwakili oleh proksi financial target, serta variabel rasionalisasi yang diwakili oleh proksi TATA, berengaruh secara positif terhadap kemungkinan adanya pelaporan keuangan yang curang. Namun, variabel kesempatan yang diwakili oleh proksi DBOUT dan variabel kapabilitas yang diwakili oleh proksi DCHANGE tidak terbukti berpengaruh terhadap kemungkinan adanya laporan keuangan yang curang.